Pengaruh Financial Knowledge Dan Financial Attitude Terhadap Personal Financial Management Behavior - Firmansyah, Irman; Indrawati , Nur Khusniyah (Jurnal Management Risiko dan Keuangan, 2024)
The purpose of this research is to analyze the effects of financial knowledge and financial attitude of university students’ personal financial management behavior. The research sample is undergraduate students of Off-Main-Campus Study Program of Brawijaya University in Kediri. The data of this research was analyzed using multiple linear regression in SPSS. This research finds that financial knowledge has no significant effect on the personal financial management behavior and that financial attitude significantly influence the personal financial management behavior. The adequate financial knowledge of the undergraduate students of Off-Main-Campus Study Program of Brawijaya University in Kediri is not followed by equal financial attitudes. Financial knowledge alone is not sufficient to ensure good personal financial management behavior. In order to have good personal financial management behavior, a good application of financial attitude is also necessary. Financial planning, saving habit, budget preparation, and correct investment need to be trained and enhanced so that all financial matters can be well managed. The relationship between financial knowledge, financial attitude, and personal financial management behavior is dynamic and sometimes reciprocal.   Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh financial knowledge dan financial attitude terhadap personal financial management behavior mahasiswa. Sampel penelitian ini adalah 93 responden, yaitu mahasiswa s-1 PSDKU Universitas Brawijaya Kediri. Teknik analisis data menggunakan regresi linear berganda dengan program SPSS. Hasil penelitian menunjukkan bahwa variable financial knowledge tidak berpengaruh signifikan terhadap personal financial management behavior. Sedangkan variabel financial attitude berpengarh signifikan terhadap personal financial management behavior. Mahasiswa s-1 PSDKU Universitas Brawijaya Kediri memiliki financial knowledge yang baik akan tetapi tidak diikuti dengan penerapan financial attitude yang baik. Financial knowledge saja tidak cukup untuk memastikan personal financial management behavior yang baik. Untuk dapat memiliki personal financial management behavior yang baik, diperlukan penerapan financial attitude yang baik pula. Kegiatan perencanaan keuangan, kebiasaan menabung, penyusunan anggaran, dan berinvestasi dengan benar perlu dilatih dan ditingkatkan sehingga seluruh keuangan dapat dikelola dengan baik. Hubungan antara financial knowledge, financial attitude, dan personal financial management behavior bersifat dinamis dan terkadang memiliki hubungan timbal balik.